S17 The burden of idiopathic pulmonary fibrosis in the united kingdom: a retrospective, matched cohort study. (15th November 2016) - Storm, M; Tran, I; Strongman, H; Fredriksson, J; Maher, T
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a specific form of chronic, progressive fibrosing interstitial pneumonia which primarily affects older adults, for which very few treatments have existed. While attention has been paid to quantifying the rising incidence and prevalence of the disease, little has been done to quantify the impact of this disease on NHS resources and how this impact varies by setting. Objective: This study aims to identify health care utilisation patterns in the United Kingdom (UK) following IPF diagnosis. Methods: The Clinical Practice Research Datalink (CPRD) GOLD dataset for general practitioner office visits and the linked Hospital Episode Statistics (HES) datasets were analysed, covering the time period from January 1, 2000 to June 30, 2015. A matched cohort analysis was conducted, and frequency counts and regression analyses were used to quantify raw healthcare resource utilisation and understand the proportion of the utilisation that is attributable to IPF. Results: The results of this study indicate that IPF patients have significantly higher healthcare utilisation patterns than non-IPF patients. The regression results indicate that IPF leads to roughly 2.2 times as many GP visits, 8.7 times as many inpatient hospitalizations, and 2.4 times as many outpatient hospital visits per year (all p-values <0.0001), as well as increased referrals, prescriptions, and, in the post-diagnosis period, inpatient stay duration. Additionally, healthcare utilisation amongst these patients is dramatically higher in the year prior to IPF diagnosis, a pattern not witnessed in the matched cohort. Conclusions: IPF imposes a significant burden on the NHS despite its rare prevalence. IPF patients experience an across the board increase in healthcare utilisation, but the burden is particularly acute in the inpatient hospital setting. Additionally, the large increase in resource utilisation in the year prior to IPF diagnosis is evidence of the potential benefits to refining the diagnostic procedures.